Komparasi Hasil Belajar Matematika Ditinjau dari Kelengkapan Fasilitas Belajar dan Motivasi Siswa Kelas VII SMP N 23 Surakarta - Samson, Zuraida Mushlihah, Drs. Ariyanto, M.Pd (2017)
The purpose of this research is to analyse and exam: (1) the differencein mathematics learning outcomes of learning facilities appliance, (2) the differencein mathematics learning outcomes of motivation , (3) the interaction of learning facility appliance and motivation toward the mathematics learning outcomes. This is quantitative research with expost facto design. The population is all student of SMP N 23 Surakarta class VII. The sample of student are 60 students with cluster random sampling technique. The gatering data uses questionaire and documentation. Data analytical technique uses two ways varian analysis with to different cell. The research result with α = 5% is: (1) there is no influence of learning facility toward the mathematics learning outcome, (2) there is no influence motivation toward the mathematics learning outcomes, (3) there is no interaction between learning facility applience and motivation toward mathematics outcomes Keyword: mathematics learning outcomes, learning facility appliance, motivation